KARAKTERISTIK EKSTERIOR, PRODUKSI DAN KUALITAS TELUR ITIK ALABIO (Anas platyrhynchos Borneo) DI SENTRA PETERNAKAN ITIK KALIMANTAN SELATAN - Abrani Sulaiman; S. N. Rahmatullah (Bioscientiae, 2011)
Alabio duck as one of the genetic resources of South Kalimantan develop rapidly and well-known as an excellent breed of ducks for egg production in Indonesia. However, due to unplanned crossbreeding in the field, presumely  the productivity and the purity of Alabio ducks decreased.   The study is conducted in order to provide information of the characteristics of body weight, body shape, colour of feather, beak, and shank, and also egg production and egg quality of Alabio ducks at duck farming centers in South Kalimantan.  The results indicated that there are uniformity in body weight,  ≤ 1,5 – 1,6 kg for female and  > 1,6 kg for male at 20-24 weeks of age, bottle for of body shape, 60o elavation, but there are variations in some degree in feather colour, beak colour and shank colour of Alabio duks. The feathers vary between batik (strip) or not-strip with cream as the base color. Meanwhile, the colour of beak and shank vary as light yellow, old yellow and orange.  Unless for the higher egg production (91%) in the intensive system and yellow red yolk colour (12,93 RYCF) in the extensive system, egg qualities are not different between production systems.